Are the main destinations the main producers of tourism research too? The spanish experience - Vargas Sánchez, Alfonso (2017)
It is unconceivable today a model of tourism development without a strong connection to the scientificresearch community, according to the triple helix model, authored by Etzkowitz (2008). This is why we haveanalyzed the relationship that might exist between the importance of tourism in a country or region and the weightof its international scientific output. In this sense, we have seen the growth experienced during this century by theSpanish scientific production, which has been placed, in line with its weight in the world tourism, as one of theleading countries in research, although still far from the hegemony of the United States and United Kingdom.Nationally, the contribution of regions and universities to the generation of scientific knowledge at internationallevel has been also identified, as well as major journals in which the papers have been published.